Scarborough from Ft. King George, Tobago - Martin, Barbara (Unimax Ltd.,[Trinidad and Tobago], 2011)
The postcard shows a view of Fort King George in Tobago, which was built in the 1770s by the British.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fortification--Trinidad and Tobago; Cities and towns--Scarborough; Historic sites; Fort King George